Game-matching background music has an add-on effect for reducing emotionality of traumatic memories during reconsolidation intervention - Jiang, Che; Chen, Wei; Tao, Ling; Wang, Jiajia; Cheng, Kuihong; Zhang, Yibo; Qi, Zijuan; Zheng, Xifu (Frontiers in Psychiatry, 2023)
Hospital is a stressful place of employment, and a high proportion of healthcare workers, especially the ICU (Intensive Care Unit) nurses were found to be at risk of PTSD. Previous studies showed that taxing working memory through visuospatial tasks during the reconsolidation process of aversive memories can reduce the number of intrusions afterwards. However, the finds could not be replicated by some researches, indicating there may be some boundary conditions that are subtle and complex. We performed a randomized controlled trial (ChiCTR2200055921). In our study, a series of ICU nurses or probationers who performed a cardiopulmonary resuscitation (CPR) were enrolled and instructed to play a visuospatial music tapping game ("Ceaseless Music Note", CMN; Beijing Muyuan Technology Co., Ltd., Beijing, China) at the fourth day after CPR. The number of intrusions each day were recorded from the first to the seventh days (24 h×6 day), and the vividness and emotionality of CPR memories were rated at the 4th and 7th days. These parameters were compared between different groups (game with background sound; game with sound off; sound only; none). Our results showed that the game-matching background music can have an add-on effect for single tapping game with no sound in reducing the emotionality of previous aversive memories. We proposed that flow experience (the subjective experience of effortless attention, reduced self-awareness, and enjoyment, and may be induced by optimal skill-demands compatibility in challenging tasks) as a key boundary condition for successful reconsolidation intervention.